2019
DOI: 10.1177/1055665619838381
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Consanguinity on Familial Clefting Among Palestinians

Abstract: Introduction: Orofacial clefts (OFC) are the most common congenital craniofacial anomaly. The relationship between intermarriage (consanguinity) and positive family history for OFC is not well described. Consanguinity rates in developed countries are <1% but are considerably higher in the Middle East (45%). Familial clefting rates in developed countries are under 20% but in the Middle East are reported at 30% or higher. Objective: To determine OFC demographics and to clarify the relationship between consang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
3
4
0
1
Order By: Relevance
“…Rajeev et al 35 found that parental consanguinity was significantly associated with CP ( P = 0.04), but not with cleft lip with or without cleft palate. Similar conclusion was reported by Sabbagh et al 30 and Saeed et al 31 On the other hand Leite and Koifman 36 found parental consanguinity was associated only with CL/P (OR = 3.8, 1.27–12.18).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Rajeev et al 35 found that parental consanguinity was significantly associated with CP ( P = 0.04), but not with cleft lip with or without cleft palate. Similar conclusion was reported by Sabbagh et al 30 and Saeed et al 31 On the other hand Leite and Koifman 36 found parental consanguinity was associated only with CL/P (OR = 3.8, 1.27–12.18).…”
Section: Discussionsupporting
confidence: 87%
“…Although all types of OFCs had positive correlation with parental consanguinity, the relationship was only statistically significant for the CP type, with a doubling of the risk, particularly for first cousin marriages 30 . This finding was close to the frequency of consanguineous marriage among OFCs sample of Palestinian population, where they found a frequency of 53% of parental consanguinity 31 . It is worth noting that Jordanian, Saudi Arabian, and Palestinian populations are all of Arab ethnicity, an ethnicity that is known for its genetic heterogeneity, which might explain some of the variation found between discussed studies 32 …”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…13 According to research conducted in India, left-sided unilateral NS CL/P clefts in children were more prevalent than their right-sided counterparts. 14 Given that the right-sided fetal head arteries leave the aortic arch closer to the heart, it has been hypothesized that the right side may have a better hemodynamic perfusion. One of the risk factors for NS CB/P diseases is consanguinity.…”
Section: Discussionmentioning
confidence: 99%
“…El paladar hendido y labio leporino son las malformaciones congénitas más comunes de la cabeza y cuello en Irán. En un estudio realizado en 2017, se encontró que el matrimonio consanguíneo se asocia fuertemente (OR=3,2; IC95%:1,9-5,3) con una mayor incidencia de esta anomalía [34], en tanto que en Palestina se encontró que en los pacientes con paladar hendido la tasa de consanguinidad era del 67% [35].…”
Section: Anomalías Congénitas Y Patologías Asociadas a Consanguinidadunclassified